Behçet Disease. Issue 1 (9th November 2022) - Di Dier, Kelly; Leenknegt, Benjamin; Lemmerling, Marc
Teaching Point: Although Behçet disease is a multisystemic and chronic vasculitis, it can be superimposed with a variety of acute vasculitis.